The Complexity of Families Involved in High-Conflict Disputes: A Postseparation Ecological Transactional Framework. Issue 2 (17th February 2019) - Polak, Shely; Saini, Michael
ABSTRACT: The use of the term 'high conflict' to describe a wide range of family dynamics after separation and divorce has increased significantly over the years. At the moment, no consensus on the definition of high conflict exists. Lack of definitional clarity hinders the ability for legal and mental health professionals to assess, identify, and effectively intervene with this population. Based on a rapid evidence assessment of 65 empirically based social science studies relevant to high conflict, this article positions high-conflict separation and divorce using an ecological transactional model to better understand risk factors and indicators associated with these families. Authors propose a more comprehensive definition that captures the complexity and interactions of various risk factors and indicators on multiple levels. Positioning high-conflict families using an ecological model identifies several points of intervention professionals can use and the fundamental need for collaboration among stakeholders for effective intervention.